Attitude toward death in nursing staffs in hospitals of Rafsanjan (south east Iran) - Mohammad Asadpour; Reza Bidaki; Zahra Rajabi; Seyed Ali Mostafav Mostafavi; Zaheeraddin Khaje-Karimaddini; Mohammad Javad Ghorbanpoor (Tehran University of Medical Sciences, 2015)
Background & Aim: Fear of death can cause death anxiety for everyone. In health care professions, death anxiety becomes a routine source of stress and may lead to unwanted consequences. Coping strategies of nurses and different approaches to death can affect the quality of health care services. The aim of this study was to determine attitudes toward death in nursing staff in hospitals of Rafsanjan. Methods & Materials: This was a cross-sectional study. The population study consisted of 400 (all nursing staff) working in hospitals of Rafsanjan University of Medical Sciences (RUMS) in 2012. The data were collected using demographic and death attitude profile revised questionnaires. Results: Fear of death was significantly higher in women, younger participants with little work experience, those without experience of intensive care unit working, and those without a history of education about death (P < 0.0500). Death escape scores were significantly higher in the age group of 31-35 years. An approach toward death was significantly better in women, those with related training, those older than 46 years, and those with over 20 years of work experience. Conclusion: RUMS treatment centers had a favorable attitude toward death in five categories. This is probably due to religious beliefs and looking at death as a bridge to the afterlife.